دلالة المكـان فــي رواية حائـط المبكى -عز الدين جلاوجي- - عوينات, عربية; صادقي, كوثر; غنايم, نجاة (University of El-oued, 2022)
تحتوي رواية "عز الدين جلاوجي " على العديد من العناصر والمكونات السردية التي تتفاعل فيها، ومن أهم العناصر التي برزت هي عنصر المكان الذي قد جسده الروائي في روايته، وأعطاه الجزء الكبير في الرواية وربطه بجميع العناصر الأخرى، فقد لاحظنا تغير للأماكن التي شهدناها في الرواية وهذا راجع لتغير الحالة النفسية التي يعيشها البطل. The novel "Izz al-Din Jalawji" contains the elements and elements that consist of the elements that interact in it, and one of the most important elements that emerged is the element that the novelist embodied in his novel, and gave him the large part in the novel and linked it to all other elements, we have noticed a change in the places that we witnessed in the novel and this See the change in the psychological state of the hero
Keywords: دلالة المكـان - رواية حائـط المبكى - عز الدين جلاوجي; The Sign of the Place - The Wailing Wall Novel - Izz al-Din Jalawji